Venusberg / by Anthony Powell. - Powell, Anthony, 1905-2000. (Masterworks of fiction., 2003)
"Lushington, a serious young man who believes implicitly in progress, is posted as special correspondent to an obscure Baltic state. There, in the unstable political situation, he hopes to find some newsworthy stories and to forget a failed love affair. But in the frivolous, party-going capital Lushington becomes involved with some decidedly eccentric individuals - the egregious valet, Pope, known to his army comrades as "the Duke," the ostentatious Count Bobel, who sells face cream and smells of brilliantine, and the mysterious Frau Mavrin, all of whom involve Lushington and the reader in a wry and sophisticated dialogue."--Jacket.